Investigating the prevalence of chronic diseases in the elderly and the factors affecting them in urban and rural centers of the cities covered by Ahvaz Jundishapur University of Medical Sciences - Shams, Firouzeh; Eftekhar Ardabili, Hasan; Andaje Garmarodi, Gholam Reza; Keshavarzian, Ehsan (Journal of Neonatal Surgery, 2025)
Background and Purpose: The present study investigated the prevalence of chronic diseases in the elderly and the factors affecting them. Methods: The sample size of the present study was 418 people selected among all elderly who were aged over 60 years, eligible for the research population, and were living in urban and rural centers of the cities covered by Ahvaz Jundishapur University of Medical Sciences. The research instrument was a researcher-made questionnaire with the necessary validity and reliability. The research design was descriptive-analytical (cross-sectional). Statistical models, including the Chi-square test, were used to analyze the data. The data were analyzed in SPSS-16 software. Results: In this study, chronic diseases in the elderly were 90.19%. The four most common chronic diseases in this study were: vision problems with 57.2%, musculoskeletal diseases with 51.3%, digestive diseases with 46%, and hypertension with 45%. Conclusion: The study revealed a significant relationship between age, ethnicity, physical activity, and the prevalence of chronic diseases. There was no statistically significant relationship between the prevalence of chronic diseases in the elderly and factors such as gender, education, job, nutrition, body mass index, smoking, and drug use.